2014
DOI: 10.3389/fimmu.2014.00316
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Review of Toll-Like Receptor 4 Expression and Functionality in Different Animal Species

Abstract: Toll-like receptors (TLRs) belong to the pattern recognition receptor (PRR) family, a key component of the innate immune system. TLRs detect invading pathogens and initiate an immediate immune response to them, followed by a long-lasting adaptive immune response. Activation of TLRs leads to the synthesis of pro-inflammatory cytokines and chemokines and the expression of co-stimulatory molecules. TLR4 specifically recognizes bacterial lipopolysaccharide, along with several other components of pathogens and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
557
3
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 681 publications
(578 citation statements)
references
References 108 publications
7
557
3
11
Order By: Relevance
“…MD-2 acts as a coreceptor for recognition of both exogenous ligands (43,44) and endogenous ligands (45,46). In addition, TLR4 can bind bacterial and viral PAMPs and, under inflammatory conditions, also endogenous damage-associated molecular pattern molecules (9). Importantly, the amino acid variability in the extracellular TLR4 ligand recognition domain changes the affinity for different agonists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MD-2 acts as a coreceptor for recognition of both exogenous ligands (43,44) and endogenous ligands (45,46). In addition, TLR4 can bind bacterial and viral PAMPs and, under inflammatory conditions, also endogenous damage-associated molecular pattern molecules (9). Importantly, the amino acid variability in the extracellular TLR4 ligand recognition domain changes the affinity for different agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the amino acid variability in the extracellular TLR4 ligand recognition domain changes the affinity for different agonists. The extracellular domains of mouse and human TLR4 show only 62% sequence similarity, while the hypervariable ligand binding regions have only 48% sequence similarity (9,47). Moreover, species differences for MD-2, the coreceptor for TLR4, also affect the ligand recognition (48,49) and the structural basis for these species differences has been resolved (50), which highlights the differences in PAMP recognition between mouse TLR4 and human TLR4 (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were abrogated in the presence of PAFR antagonists or anti-CD36 blocking antibody [17]. Comparing to macrophages, DCs express less CD36 [32,33] and TLR4 in the membrane [34], thus these mechanisms above mentioned for macrophages are less significant in DCs. Additionally, it was demonstrated that PAFR activation induced CD36 expression in macrophages by mechanisms dependent on PPARγ [17].…”
Section: Discussionmentioning
confidence: 82%
“…However, one major difference between human and mice DCs is the differential expression of TLRs. For example, human DCs only express low levels of TLR4 when compared with their mouse counterparts [42,43]. While lower TLR4 expression corresponds to a weaker response to LPS [44], a higher dose of LPS can still initiate DC activation [45].…”
Section: Discussionmentioning
confidence: 99%